An Analysis of Test Items of English Subject at Eighth Grade of SMP Muhammadiyah Pasir Pengaraian - Merry Prima Dewi, Arlen Mellani, Syahrul, Reflinda, (Education Achievement: Journal of Science and Research, 2023)
This research is aimed at describing the quality of the English tests and the index of difficulty. This research was conducted because of the researcher found several problems faced by eighth students grade of SMP Muhammadiyah Pasir Pengaraian when submitted the examination result. These problems were most of students had limited vocabularies so they could not answer the question of the test, they could not understand the question because it did not have clear. Based on the problems above this research is aimed at describe the quality of test that used in final examination. This research is descriptive quantitative research. The population of the research were all of the eighth grade students at SMP Muhammadiyah Pasir Pengaraian. They were 84 students as the sample of the research. The instrument of the research were documentation in the form of the sheet of the students’ test and it was analyzed by using Ms. Excel. Based on the result of the research, there were 30 questions answered by the students. According to the categories of the questions as follows; 34 students they were belong to easy test (40%), 25 students answered difficult test, they were belong to difficult test (30%) and 42 students answered moderate test. They were belong to moderate test(50%). The kinds of test were matching word, arranging the statement, essay and multiple choice items. English test were included in moderate tests. The tests were good but there were some unclear instructions so that most of students could not answer. It can be concluded that arrangement of the question were good, but the form of the questions have did not clear instructions, so most of the students did not understand the questions because of the meaning of the vocabulary most of them did not know. Therefore the teacher must have the knowledge to make good quality questions so that students can answer the questions.